Designing higher education to promote more time on studies and divergent learning outcomes: an instructional designer’s perspective - Järnerot, Anna (Frontiers in Education, 2025)
The article presents a design-based study. The intention was to increase student teachers’ utilization of study time, fostering enhanced learning. The design used flipped classroom principles combined with the students’ creation of websites. Two distinct phases in teaching design development in a Norwegian teacher education program are presented, and shortcomings and successes are discussed.